Imagining the city in lockdown: Place in the COVID-19 self-recordings of the Lothian Diary Project - Cowie, Claire; Hall-Lew, Lauren; Elliott, Zuzana; Klingler, Anita; Markl, Nina; McNulty, Stephen Joseph (Frontiers in Artificial Intelligence, 2022)
The COVID-19 pandemic brought about a profound change to the organisation of space and time in our daily lives. In this paper we analyse the self-recorded audio/video diaries made by residents of Edinburgh and the Lothian counties during the first national lockdown. We identify three ways in which diarists orient to the changes in ‘chronotopes’, or, shifts in the representation of place, in the times before versus the times after lockdown. We argue that the act of making a diary for an audience of the future prompts diarists to produce different kinds of chronotopes, and each of these different orientations illuminates the differential impact of the COVID-19 lockdowns across the community.